Group C beta hemolytic Streptococci as a potential pathogen in patients presenting with an uncomplicated acute sore throat - a systematic literature review and meta-analysis - Ronny Kent Gunnarsson; Naveen Manchal (Taylor & Francis Group, 2020)
Objective: The pathogenicity of beta-hemolytic Streptococcus group C (GCS) in patients attending for an uncomplicated acute sore throat is unknown and it was the objective to clarify this. Design: Systematic literature review with meta-analysis. Setting Medline and Scopus were searched from inception to February 2019, with searches of reference lists, Subjects case-control studies stating prevalence of GCS in patients as well as healthy controls presented for children and adults separately. Studies including patients already treated with antibiotics and studies focused on patients with HIV, malignancy or immunosuppression were not included. Main outcome measures Pooled prevalence of GCS was compared between patients and controls using chi-square and was further explored by calculating the positive etiologic predictive value (P-EPV) showing the post-test probability of a link between a sore throat and the bacterial finding. P-EPV for GCS was compared with that for group A Streptococci (GAS) using figures from the same publications and patients. Results: Eleven studies were included. The prevalence of GCS among patients versus controls was similar in children (3.15 versus 2.87%, p = .44) but for adults higher in patients (11%) than in controls (5.6%) (p < .0001). The P-EPV for finding GCS in children with a sore throat was 9.3% (0.0-41%). The corresponding P-EPV for GCS in adults with a sore throat was 53% (36-67%) while the corresponding P-EPV for GAS in adults was 94% (90-96%). Conclusions: GCS do not seem associated with the uncomplicated acute sore throat in children but there is support for an association in adults being weaker than for GAS. A possible consequence is to ignore GCS in otherwise healthy patients at their first visit for an uncomplicated sore throat. This would enable a stronger focus on the use of modern point of care tests (POCTs) to detect GAS.Key points There is no current consensus on the pathogenicity of group C beta-hemolytic Streptococcus (GCS) in patients attending for an uncomplicated acute sore throat. This systematic literature review concludes it is unlikely that GCS is involved in the uncomplicated sore throat in otherwise healthy children. This meta-analysis found a moderate link between GCS and the uncomplicated sore throat in adults. The link in adults between GCS and the sore throat is much weaker than the corresponding link for group A beta-hemolytic Streptococcus.